2002
DOI: 10.1074/jbc.c200263200
|View full text |Cite
|
Sign up to set email alerts
|

N-terminal Activation Is an Essential Early Step in the Mechanism of Action of the Bacillus thuringiensis Cry1Ac Insecticidal Toxin

Abstract: A variant form of the Bacillus thuringiensis Cry1Ac toxin that is not cleaved at the N terminus during proteolytic activation with trypsin was found to be incapable of forming pores in Manduca sexta brush border membrane vesicles in vitro and had reduced insecticidal activity in vivo. Binding studies indicated an altered binding pattern of the mutant toxin in that bound toxin could not be fully displaced by a high molar excess of fully trypsin-activated toxin. These results suggest that proteolytic removal of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
38
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(41 citation statements)
references
References 10 publications
3
38
0
Order By: Relevance
“…Anilkumar et al (1) suggested that this observation may be indicative of a differential activation of protoxin in the resistant insect midgut or that the C-terminal end of the fulllength protein contained in the protoxin may protect the active toxin from the degradative action of midgut proteases, resulting in a higher yield of the fully active toxin. Results presented here, in which AR1 does not lose resistance in the presence of modified toxin or protoxin (these toxins were produced by deleting part of the N-terminal portion of the protein [42] where there is relatively little cleavage during initial proteolysis [6]), is consistent with the hypothesis that the C-terminal end of the protoxin may provide protection from midgut proteases found in Cry1Ac-resistant H. zea (1).…”
Section: Fig 4 Effect Of Cry1ac Toxin On Ksupporting
confidence: 73%
“…Anilkumar et al (1) suggested that this observation may be indicative of a differential activation of protoxin in the resistant insect midgut or that the C-terminal end of the fulllength protein contained in the protoxin may protect the active toxin from the degradative action of midgut proteases, resulting in a higher yield of the fully active toxin. Results presented here, in which AR1 does not lose resistance in the presence of modified toxin or protoxin (these toxins were produced by deleting part of the N-terminal portion of the protein [42] where there is relatively little cleavage during initial proteolysis [6]), is consistent with the hypothesis that the C-terminal end of the protoxin may provide protection from midgut proteases found in Cry1Ac-resistant H. zea (1).…”
Section: Fig 4 Effect Of Cry1ac Toxin On Ksupporting
confidence: 73%
“…There were reports that the N terminus may prevent the interaction of toxin with target membrane, and the removal of the N-terminal peptide is a necessary step in toxin activation. In addition, the C terminus is believed to be important for crystallization and may by extension apply to the activity of Cry toxin, but it is not required for insecticidal activity (6). Therefore, the cleavages of the N terminus and C terminus may enhance the insecticidal activity of Cry protein.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, an in-depth study on the synthesis mechanisms of B. thuringiensis parasporal crystals and spores under different physiologically relevant conditions at the proteomic level is highly significant. To date, most B. thuringiensis proteomic studies have mainly focused on parasporal crystal purification and identification (7,52), spore composition and function (13,22), classification of Bacillus strains (16), and so on. There has been no report on the large-scale characterization of the B. thuringiensis proteome, which is becoming one of the international hot spots of research.…”
mentioning
confidence: 99%